Immune phenotypes of prostate cancer cells: Evidence of epithelial immune cell-like transition? - Dong Lin; Xinya Wang; Stephen Yiu Chuen Choi; Xinpei Ci; Xin Dong; Yuzhuo Wang (Asian Journal of Urology)
Prostate cancers (PCa) have been reported to actively suppress antitumor immune responses by creating an immune-suppressive microenvironment. There is mounting evidence that PCas may undergo an ‘‘Epithelial Immune Cell-like Transition’’ (EIT) by expressing molecules conventionally associated with immune cells (e.g., a variety of cytokines/receptors, immune transcription factors, Ig motifs, and immune checkpoint molecules), which subsequently results in the suppression of anti-cancer immune activity within the tumor microenvironment. Recent progress within the field of immune therapy has underscored the importance of immune checkpoint molecules in cancer development, thus leading to the development of novel immunotherapeutic approaches. Here, we review the expression of select immune checkpoint molecules in PCa epithelial and associated immune cells, with particular emphasis on clinical data supporting the concept of an EIT-mediated phenotype in PCa. Furthermore, we summarize current advances in anti-immune checkpoint therapies, and provide perspectives on their potential applicability. Keywords: Prostate cancer, Immune checkpoint, Epithelial immune cell-like transition, Immune suppression, Immune therapy